Quality evaluation of Systematic Reviews (PRISMA, AMSTAR-2) of platelet rich plasma as a method of tissue regeneration in odontology. - Carolina Garcés; Francesca Burattini; Valeria Flores (Universidad de Concepción., 2019)
To evaluate methodologically (PRISMA) and report (AMSTAR-2) quality of systematic reviews regarding platelet rich plasma (PRP) as a method of tissue regeneration in dental procedures. Material and Methods: A search of systematic reviews (SR) of PRP was performed in the databases PUBMED, EBSCO, The Cochrane Library, Web of Science, Lilacs, Epistemonikos, and supplemented by manual review of the bibliography of the selected articles. Covering articles published from January 2008 to August 2018, in English or Spanish. The advanced search was performed using Boolean terms AND and OR. The quality of the SRs was evaluated with the PRISMA guidelines, and the methodological quality was evaluated with the checklist of the AMSTAR-2 tool. Result: Seventeen SRs were selected. From the selected articles, 11 were cataloged as of Very good quality, three as Good and three as Moderate. Regarding the methodological quality, two articles were classified as Critically Low, one as Low, 10 Moderate and four as High quality. Conclusion: Most SRs are of high quality regarding their report and methodology, and provide an accurate summary of the results of the primary studies available. However, there is a lower percentage of RS whose methodological and drafting deficiencies make their results and conclusions unreliable, and therefore, their clinical applicability is questionable, and offer a wrong clinical vision, which is not the best and safest therapeutic measure for patients and may compromise their well-being.